Pengaruh Sosial Media Marketing Terhadap Minat Beli Konsumen Pada Online Shop 3sshop di Samarinda - Dyah Kusrihandayani; Indah Martati; Suminto Suminto; Alliya Alliya (Politeknik Negeri Samarinda, 2021)
The presence of internet technology has changed various behaviors and people's mindsets in buying and selling transactions. When the Covid-19 pandemic hit from the end of 2019, people's attitudes were limited in their work, responsibilities and activities, it was a must to do it online. The purpose of this study is to analyze and prove whether social media marketing has a significant influence on buying interest in the 3sshop online shop in Samarinda. The research method used is quantitative research. The analytical tool used is simple regression analysis where the respondents selected are consumers who have shopped at the online shop 3sshop with a total of 90 respondents. The sampling technique uses non-probability sampling, which is more precisely Convenience Sampling. This research instrument uses a questionnaire surveyed through a google form. The indicators used to measure social media marketing are: online communities, interaction, sharing of content, accessibility, credibility. While the indicators to measure buying interest are transactional interest, referential interest, preferential interest, and exploratory interest. The results show that there is a significant influence of social media marketing on the interest in buying online shop 3sshop in Samarinda.